Reflections on The Maitrakanyaka-Avadana at Candi Borobudur: The Teaching of Exchanging and Equalizing - So Tju Shinta Lee; Salim Lee (Penerbit BRIN (BRIN Publishing), 2025)
Abstrak. Refleksi tentang Maitrakanyaka-avadana di Candi Borobudur: Ajaran “Menukar dan Menyamakan